2022
DOI: 10.3390/ijms23105407
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Expansin Genes in Wild Soybean (Glycine soja) and Functional Characterization of Expansin B1 (GsEXPB1) in Soybean Hair Root

Abstract: Wild soybean, the progenitor and close relative of cultivated soybean, has an excellent environmental adaptation ability and abundant resistance genes. Expansins, as a class of cell wall relaxation proteins, have important functions in regulating plant growth and stress resistance. In the present study, we identified a total of 75 members of the expansin family on the basis of recent genomic data published for wild soybean. The predicted results of promoter elements structure showed that wild soybean expansin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Collectively, our findings demonstrate the effectiveness of pHOG13 and pHGUS7 as new tools for enhancing the transformation efficiency of A. rhizogenes K599 in hairy root studies. The K599 strain is effective in transforming several species, including the legumes G. max (soybean; Kereszt et al, 2007;Lin et al, 2011;Zhang et al, 2021;Chu et al, 2022), G. soja (wild soybean; Feng et al, 2022;Li et al, 2024), P. vulgaris (common bean;Estrada-Navarrete et al, 2007;Ferguson et al, 2014), P. sativum (pea; e.g. Li et al, 2023), Lens culinaris (lentil; Foti and Pavli, 2020), Cicer arietinum (chickpea; Aggarwal et al, 2018), Vigna radiata (mungbean; Cuong et al, 2023;Lin et al, 2022;, Vigna unguiculata (cowpea; Ji et al, 2019), Cajanus cajan (pigeon pea; Meng et al, 2019), and non-legumes such as Gossypium hirsutum (cotton; Zhou et al, 2022), citrus species (Ma et al, 2022;Gong et al, 2024), Cucumis sativus (cucumber; Nguyen et al, 2022), Cucurbita moschata (pumpkin; Geng et al, 2022), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our findings demonstrate the effectiveness of pHOG13 and pHGUS7 as new tools for enhancing the transformation efficiency of A. rhizogenes K599 in hairy root studies. The K599 strain is effective in transforming several species, including the legumes G. max (soybean; Kereszt et al, 2007;Lin et al, 2011;Zhang et al, 2021;Chu et al, 2022), G. soja (wild soybean; Feng et al, 2022;Li et al, 2024), P. vulgaris (common bean;Estrada-Navarrete et al, 2007;Ferguson et al, 2014), P. sativum (pea; e.g. Li et al, 2023), Lens culinaris (lentil; Foti and Pavli, 2020), Cicer arietinum (chickpea; Aggarwal et al, 2018), Vigna radiata (mungbean; Cuong et al, 2023;Lin et al, 2022;, Vigna unguiculata (cowpea; Ji et al, 2019), Cajanus cajan (pigeon pea; Meng et al, 2019), and non-legumes such as Gossypium hirsutum (cotton; Zhou et al, 2022), citrus species (Ma et al, 2022;Gong et al, 2024), Cucumis sativus (cucumber; Nguyen et al, 2022), Cucurbita moschata (pumpkin; Geng et al, 2022), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Another study identified 75 members of the expansin ( EXP ) family in wild soybean ( Glycine soja ). In the identified 75 members of the expansin ( EXP ) family, overexpression of GsEXPB1 increased the number of hairy root and tolerance to salt stress [ 4 ]. Sehrish et al identified 122 SET domain genes ( SDGs ) genes in B.napus and characterized their evolution, structure and expression patterns in detail [ 5 ].…”
Section: Genome-wide Characterization Of Gene Families In Plantsmentioning
confidence: 99%
“…The expansin gene family in wild soybeans may be of great significance for soybean molecular breeding, but related research is scarce. Our research group completed the whole-genome identification of the wild soybean expansin family in a previous study and analyzed the expression patterns of some expansin genes [ 35 ]. Previous studies have shown that GsEXLB14 is specifically transcribed in wild soybean roots, and its transcript levels are significantly upregulated under salt and drought stress treatments.…”
Section: Introductionmentioning
confidence: 99%